Enhanced Removal Efficiency of Malachite Green Dye Using Gambir Leaf Extract-Modified NiFe LDH Composites: A Study of Cationic Dye Adsorption - Jefri, Jefri; Fithri, Najma Annuria; Lesbani, Aldes (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
A NiFe layered double hydroxide (LDH) composite with Uncaria gambir (UG) leaf extract was successfully synthesized. The composite (NiFe-UG LDH) and the base material (NiFe LDH) were identified using X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), and Brunauer-Emmett-Teller (BET) Surface Area techniques. The XRD and FTIR results revealed the incorporation of gambier leaf extract into the NiFe LDH structure, as indicated by the combined diffraction patterns and spectral features. The BET analysis indicated a decrease in the surface area of NiFe-UG LDH compared to that of NiFe LDH, suggesting that active compounds from the gambier leaf extract effectively coated the LDH surface and blocked its pores. During malachite green (MG) adsorption, NiFe-UG demonstrated faster adsorption kinetics and a higher adsorption efficiency, reaching 96.420% compared to 92.085% for NiFe LDH. While both materials followed pseudo-first-order kinetics, their isotherm behaviors differed: NiFe-UG adhered to the Langmuir model, indicating monolayer adsorption, whereas NiFe LDH followed the Freundlich model, signifying multilayer adsorption. Further analysis suggested that adsorption in NiFe LDH was primarily governed by physisorption, while in NiFe-UG, a combined physisorption-chemisorption mechanism occurred. These results underscore the enhanced adsorption capacity of the composite material, attributed to the introduction of additional functional groups from the gambier leaf extract. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).